The inclusion toolkit - Herbert, Sarah (London : SAGE, 2011)
This book is aimed at the teacher who wishes to respond to the diversity of learning needs of children who are placed within their mainstream classroom, without teaching each child differently.
Includes bibliographical references and index
EDU